2018
DOI: 10.3389/fmicb.2018.00951
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Microbial Signatures Associated With Different Breast Cancer Types

Abstract: A dysbiotic microbiome can potentially contribute to the pathogenesis of many different diseases including cancer. Breast cancer is the second leading cause of cancer death in women. Thus, we investigated the diversity of the microbiome in the four major types of breast cancer: endocrine receptor (ER) positive, triple positive, Her2 positive and triple negative breast cancers. Using a whole genome and transcriptome amplification and a pan-pathogen microarray (PathoChip) strategy, we detected unique and common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
192
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(206 citation statements)
references
References 46 publications
13
192
0
1
Order By: Relevance
“…1 The largest study to examine microbes and BC was from The Cancer Genome Atlas (TCGA) wherein Proteobacteria, Actinobacteria, and Firmicutes were shown as the most abundant phyla in breast tumors, which is consistent with our work and others, and reminiscent of the gut. 1,11,14,18,21,168,[172][173][174][175][176]180,181 We detected dysbiosis in breast tumors and tumor-adjacent breast tissue compared to normal tissue from healthy subjects. Recall that Ruminococcus is high in the gut of BC patients 11 and reduced by Mediterranean diet in the mammary glands of monkeys.…”
Section: While Tumors Had Lowermentioning
confidence: 87%
See 1 more Smart Citation
“…1 The largest study to examine microbes and BC was from The Cancer Genome Atlas (TCGA) wherein Proteobacteria, Actinobacteria, and Firmicutes were shown as the most abundant phyla in breast tumors, which is consistent with our work and others, and reminiscent of the gut. 1,11,14,18,21,168,[172][173][174][175][176]180,181 We detected dysbiosis in breast tumors and tumor-adjacent breast tissue compared to normal tissue from healthy subjects. Recall that Ruminococcus is high in the gut of BC patients 11 and reduced by Mediterranean diet in the mammary glands of monkeys.…”
Section: While Tumors Had Lowermentioning
confidence: 87%
“…167 Examination of the local microbiome in BC compared to normal tumor-adjacent or normal mammary gland has revealed interesting alterations. 11,14,168,[172][173][174][175][176] The Western diet is associated with obesity and poor tumor outcomes. 177 Cook et al showed for the first time that Mediterranean vs Western diet could alter mammary gland microbes, specifically increasing Lactobacillus by 10-fold and reducing Ruminococcus in the mammary gland of non-human primates.…”
Section: Crob E S In E X Tr A-inte S Tinal Tissue and C An Cermentioning
confidence: 99%
“…Moreover, a report compared four major breast cancer types with respect to their microbial signatures and described differences in their bacterial, viral, fungal, and parasitic compositions. For instance, two breast cancer subtypes (triple-negative and triple-positive) were remarkably distinct from each other, exhibiting very different microbial patterns [31]. Besides that, microbiome compositions were related with prostate health and disease.…”
Section: Microbiome and Cancermentioning
confidence: 99%
“…Recent advances in the sensitive detection of pathogens revealed that tumors harbor a diverse set of bacteria, viruses and fungi [51,52], a community, which, in analogy to the "microbiome" in the gut, has been labeled the "oncobiome" [53]. Sequencing of bacterial 16S RNA as a species-specific genetic fingerprint identified several hundred different bacterial species in each tumor [54].…”
Section: Vγ9vδ2t Cells In Cancermentioning
confidence: 99%